The Analysis of Technological Pedagogical Current Knowledge (TPACK) Variables through Student Surveys - Susanti, Nova; Sandari, Tiara; Alrizal, Alrizal; Syuhada, Siti; Muswita, Muswita; Sanova, Aulia (Universitas Jambi, Indonesia, 2024)
In facing technological developments in 21st century learning today, teachers are required to have knowledge that can integrate technology, pedagogical knowledge, and content. The purpose of this research was to analyze the Technological Pedagogical Content Knowledge (TPACK) variables through student surveys at SMA Negeri 7 Jambi. This research used a questionnaire consisting of 33 items to collect data from 272 respondents. Furthermore, data analysis used the Structural Equation Model-Partial Least Square (SEM-PLS). The findings indicate that there is a positive correlation between the TPACK variables. Of the 12 variables that have been analyzed, 10 variables have a direct correlation with other variables, and 2 variables did not have a direct correlation and have a significant effect.